CONTEMPORARY POLITICAL SCIENCE: CONSTRICTION OF THE SCIENCE AND ANNIHILATION OF THE POLITICAL? CRITICAL NOTES FOR POLITICAL STUDIES IN LATIN AMERICA (Andamios, Revista de Investigación Social, 2009)
Giovanni Sartori’s essay “Where is Political Science Going?” has generated an important polemic. In this context, this article deals with theoretical and metodological aspects of contemporary political science, especially the discussion in the Latin-American field. This article argues that a restricted vision of the “science” and of the “politics” (forgetting the “political”) has led North American political science to a crisis. Nevertheless, this situation is not a tragedy for the study of politics in Latin America, but an opportunity to check research methods and to overcome the current limits.
Keywords: Political science; epistemology; politics; the political; Latin America